(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2026)
The concept of risk communication has been used in various fields of scientific knowledge, but there is no consensus regarding its definition. The aim of this article is to discuss the concept based on the notion of transdisciplinarity and the theory of complex thought. Methodologically, the study was developed through a theoretical deepening of the notions of "communication" and "risks." In the first case, the propositions of the Latin American School of Communication were chosen to guide the discussion, taking into account the elasticity of the term from different approaches. The discussion on the definition of "risk," in turn, was framed within the approach of the vulnerability progression to disasters, which incorporates new debates such as unequal access to communication tools and disinformation. The article’s innovation lies in considering risks not only as external agents to be communicated but also as embedded within the communication process.